Uji skrining fitokimia dan pengukuran kadar total flavonoid pada ekstrak paku (Nephrolepis biserrata) dengan fraksi n-heksana, etil asetat, dan air - Razoki; Ruth Gaby Syahanaya Butar-Butar; Elfia Neswita; Novitaria Br Sembiring; Erida Novriani; Nerly Juli Pranita Simanjuntak; Enni Halimahtussa’diyah Pakpahan (Journal of Pharmaceutical and Sciences, 2023)
Nephrolepis Biserrata, including ferns and lycophytes, are a group of plants that have been around for a long time on Earth, with more than 12,000 different species. Ferns have an important role in the ecosystem, such as helping to form humus, protect the soil from erosion, maintain soil moisture, and act as pioneer plants in the early stages of forest ecosystem succession. Phytochemical screening tests can identify bioactives that are not yet visible through bags or tests that can quickly separate natural ingredients that contain certain phytochemicals and those that do not. Extraction is the activity of withdrawing soluble chemical compounds so that they are separated from insoluble materials. Extraction can be done in various ways including n-hexane which aims to remove fat, ethyl acetate which can extract semi-polar compounds, and water which is a universal solvent.The methods used in this study include maceration, phytochemical screening, fractionation, and data analysis. The results of this research conclude that secondary metabolite compounds are present in the leaves of the Nephrolepis Biserrata fern, based on positive phytochemical tests for alkaloids, phenolics, flavonoids, tannins, and triterpenoids in the ethanol fraction. The n-hexane fraction contains alkaloids, phenolics, flavonoids, tannins, steroids, and triterpenoids. The ethyl acetate fraction contains alkaloids, phenolics, flavonoids, saponins, and tannins, while the water fraction contains alkaloids, phenolics, flavonoids, and tannins. The total flavonoid content is 17.615 mg QE/g of extract. UV-Vis spectroscopy identification results indicate the presence of ???? → ????* and n→ ????* transitions.